2020
DOI: 10.1038/s41598-020-74363-8
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of meteorological parameters on pertussis infections in Chongqing, China, 2004–2018

Abstract: Evidence on the long-term influence of climatic variables on pertussis is limited. This study aims to explore the long-term quantitative relationship between weather variability and pertussis. Data on the monthly number of pertussis cases and weather parameters in Chongqing in the period of 2004–2018 were collected. Then, we used a negative binomial multivariable regression model and cointegration testing to examine the association of variations in monthly meteorological parameters and pertussis. Descriptive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Furthermore, research by Wang et al showed that monthly temperature, precipitation, air pressure and wind speed play an important role in the transmission of pertussis. 30 The areas with the highest incidence of pertussis in Hunan Province were Changsha, Yiyang, Loudi and Xiangxi Tujia, and Miao Autonomous Prefecture. As the provincial capital, Changsha City has a large population density and frequent movement of people, making it prone to infectious disease outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, research by Wang et al showed that monthly temperature, precipitation, air pressure and wind speed play an important role in the transmission of pertussis. 30 The areas with the highest incidence of pertussis in Hunan Province were Changsha, Yiyang, Loudi and Xiangxi Tujia, and Miao Autonomous Prefecture. As the provincial capital, Changsha City has a large population density and frequent movement of people, making it prone to infectious disease outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research by Wang et al showed that monthly temperature, precipitation, air pressure and wind speed play an important role in the transmission of pertussis. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have tried to explain the association between the spread of contagious diseases and meteorological parameters (Ma et al 2010, Wang et al 2020, du Prel et al 2009, Zha et al 2020, Tasci et al 2018). Most of these studies have established a strong association between weather related parameters and the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of meteorological parameters on infectious diseases has been studied extensively (Ma et al 2010, Wang et al 2020, du Prel et al 2009, Zha et al 2020, Tasci et al 2018) and from these studies it has been established that weather parameters play an important role in assisting or resisting the spread of disease in a particular region. Table 1 [9 - 13] provides a summary of reports that have previously established relationships and strong correlations between diseases and weather parameters.…”
Section: Introductionmentioning
confidence: 99%